EMPLOYING THE PROJECT LESSON IN THE DEVELOPMENT OF VOLUNTARY WORK OF THE DEPARTMENT OF ARTISTIC EDUCATION (Journal of the College of Basic Education, 2022)
Voluntary work represents an important cultural example in changing the behavior of the individual and society. However, voluntary work has been a platform to start from in the advancement of the intellectual and developmental levels in general. It is considered as an important part of the individual's education that contributes in developing the individual's and collective capacities and offering services concerning a great deal of different fields. Lately, different art directions have appeared. They emphasize the importance of the collective voluntary work. These directions claim that having such works within different disciplines may create interactive and reciprocal relations that help in building goals, which can push them to higher unexpected levels. They also can achieve educational and intellectual interactions investing the artistic creations under the field of voluntary work. The current research 'Employing the Project Lesson in the Development of Voluntary Work of the Students of the Department of Artistic Education' is written in the pursuit of the above points.This paper contains four chapters. The first chapter includes the problem of the study, its importance and the aims, which are embodied in the recognition of the impact of the project lesson in developing the voluntary work. Chapter two, however, includes two sections. The first section focuses on the art of earth and the second explains the meaning and definition of voluntary work. The third chapter deals with analyzing the samples. Finally, chapter four includes the ending results.